1995
DOI: 10.1108/08876049510094487
|View full text |Cite
|
Sign up to set email alerts
|

The effects of customer service on consumer complaining behavior

Abstract: 1998),"Customer-service provider relationships: an empirical test of a model of service quality, satisfaction and relationship-oriented outcomes"If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
226
1
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(241 citation statements)
references
References 24 publications
8
226
1
6
Order By: Relevance
“…It seems that the issue of effective complaint handling is still not adequately addressed by businesses. This apparent disregard of dealing with customer complaints effectively is surprising, especially when the seriousness of customer dissatisfaction in the short and long term is considered: Customer switching to competitor firms (Homburg and Fürst, 2005) and negative word-of-mouth (Blodgett et al, 1995;Lerman, 2006) both inevitably lead to the high costs of acquiring new customers (Hart et al, 1990).…”
Section: Importance Of Effective Complaint Handlingmentioning
confidence: 99%
“…It seems that the issue of effective complaint handling is still not adequately addressed by businesses. This apparent disregard of dealing with customer complaints effectively is surprising, especially when the seriousness of customer dissatisfaction in the short and long term is considered: Customer switching to competitor firms (Homburg and Fürst, 2005) and negative word-of-mouth (Blodgett et al, 1995;Lerman, 2006) both inevitably lead to the high costs of acquiring new customers (Hart et al, 1990).…”
Section: Importance Of Effective Complaint Handlingmentioning
confidence: 99%
“…또한 소비자 비윤리성은 인구통계학적 특성인 여성일수록, 연령, 교육수준, 소득수준이 낮을수록 높은 비윤리성과 관련이 있 는 것으로 나타났다 (Erffmeyer, et al 1999;Frederick et al, 1988;Fullerton et al, 1996;Kennedy & Lawton, 1998;Lee & Seo, 2012;Serwinek, 1992;Vitell et al, 1991;Shin, 2000;Kim & Lee 2003;Kim, 2006). et al, 1995: Jacoby & Jaccard, 1981Richins, 1983;Singh, 1988 (Seo & Song, 2006;Jung & Yeo, 2010). (Bearden & Teel, 1983;Day, 1984;Day & Landon, 1976).…”
Section: 기존 연구에서 가장 빈번하게 사용하는 소비자 비윤리unclassified
“…Scientific studies has revealed that on the behavior of consumer complaints are very important recent days (Maute&William, 1993;Blodgett et al, 1993;Barlow&Moller, 1996;Eccles & Durand, 1998;Tax et al, 1998;Blodgett&Anderson, 2000;Nyer, 2000;Liu & McClure, 2001;Maxam&Netemeyer 2002;Kim, C., Kim, S., Im, & Shin, 2003;Lam&Tang, 2003;Heung & Lam, 2003;Ndubisi & Tam, 2004;Otto et al, 2005;Blodgett, Hill ve Bakir, 2006;Lerman, 2006, Ndubisi & Tam, 2007Homburg&Andreas, 2007;Blodgett ve Li, 2007;Bolkan ve Daly, 2008;Fox, 2008;Haverila&Naumann, 2009;Hansen, Wilke ve Zaichkowsky, 2009;Ashley ve Varki, 2009;Hakimah et.al. 2010;Larivet&Brouard, 2010;Tolon&Zengin, 2011;Perkins;2012;Iyiola&Ibidunni;2013;Komunda, 2013 ).…”
Section: Literature Reviewmentioning
confidence: 99%